DESAIN DAN IMPLEMENTASI RANGKAIAN RCD SNUBBER PADA DC-DC FULL BRIDGE CONVERTER - Dhika Abiyoso Rahardianto; Waru Djuriatno; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2023)
DC-DC Converter is an important component in modern electric power systems. This converter is used to convert DC voltage from one level to another, which is indispensable in various types of applications ranging from everyday electronic equipment to industrial use. DC-DC full bridge converter is one of the commonly used power converter topologies. However, these converters often face challenges in the form of voltage spikes that can damage components and oscillations that interfere with system performance. In this study the authors designed a RCD snubber circuit that could overcome this problem. The RCD snubber circuit consists of resistors, capacitors and diodes which are connected in parallel to each MOSFET. The test results show that before the snubber circuit is installed, there is a voltage spike that reaches 2 times the input voltage to more. In addition, high-frequency oscillations occur which require 1µs and 4µs to reach steady state. After adding the RCD snubber circuit, retesting was carried out and it was found that the voltage surge had reduced to about 1.2 times the input voltage. In addition, the oscillations that occur also require faster time to reach steady state, which is only 0.4µs and 1.5µs. Based on the test results and calculations, the power dissipation on the snubber resistor is also obtained. At an input voltage of 12V, the power dissipation is 2,234% input power, then at an input voltage of 24V, the power dissipation is 2,273% input power and at an input voltage of 36V, the power dissipation is 1,983% input power. From all the test results show that the RCD snubber circuit is able to reduce the voltage spikes and also the oscillations that occur at the moment of transition. Keywords: DC-DC full bridge converter, snubber, spike, oscillation, transition, dissipation